Escola de Engenharia Industrial: a gênese do ensino superior na cidade do Rio Grande (1953-1961) - Teixeira, Vanessa Barrozo (2013)
The following dissertation aims to show how the School of Industrial Engineering emerged, (Escola de Engenharia Industrial EEI), the first institution of higher education in the city of Rio Grande, in the 1950s. The periodization of work is comprised from 1953 to 1961, as it is the time period in which the Foundation of the City of Rio Grande was created, the unit responsible for supporting the School of Industrial Engineering until mid-1960s, when the school was federalized, process which begins in 1961. In order to analyze the history of this teaching institution, there had to be a reconstruction of its early years, having as main source of information, the school culture preserved in its materiality in a variety of collections in the city of Rio Grande. In addition to the material sources, they were also conducted interviews with faculty members and students of early years of the School of Industrial Engineering, considering memory as a major source of documentation for this research. From the traces of this school culture, it was possible to recollect their first steps, addressing their spaces, professors, subjects, among many other aspects. It is worth noting the presence of some important characters in the history of the institution, emphasizing the figure of Eng. Francisco Martins Bastos, a key person, for the school could finally become a reality and launch the history of higher education in Rio Grande. His entrepreneurial nature along with his role as manager backed by the interest and investment from a group of individuals belonging to a highly educated social class and professionally stabilized, were all crucial to the emergence of this institution.